2021
DOI: 10.1111/bjso.12509
|View full text |Cite
|
Sign up to set email alerts
|

What reduces prejudice in the real world? A meta‐analysis of prejudice reduction field experiments

Abstract: Fractured intergroup relations and prejudicial attitudes based on ethnic, religious, sexuality, and genderidentity differences are a regular feature of social life across many countries (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…3 22 25 The need for effective interventions to stop homophobic language and other behaviours, and to shift homophobic sport cultures, has been repeatedly identified, 3 5 9 yet systematic reviews have found no published trials of interventions. [26][27][28] This gap in the literature reflects a long-documented lack of engagement and resourcing from politicians and sport leaders for programmes designed to address sexuality-based discrimination in sport. 3 5 29 Research suggests some sport leaders fear a backlash from athletes or parents if they take action, whereas other leaders are hesitant because they are uncertain about how to stop this pervasive behaviour.…”
Section: Original Researchmentioning
confidence: 99%
“…3 22 25 The need for effective interventions to stop homophobic language and other behaviours, and to shift homophobic sport cultures, has been repeatedly identified, 3 5 9 yet systematic reviews have found no published trials of interventions. [26][27][28] This gap in the literature reflects a long-documented lack of engagement and resourcing from politicians and sport leaders for programmes designed to address sexuality-based discrimination in sport. 3 5 29 Research suggests some sport leaders fear a backlash from athletes or parents if they take action, whereas other leaders are hesitant because they are uncertain about how to stop this pervasive behaviour.…”
Section: Original Researchmentioning
confidence: 99%
“…… Future research is needed to identify the characteristics that prejudice reduction interventions need to be scalable, and consideration should also be given to whether particular prejudice reduction interventions meet those criteria. (Hsieh et al, 2022, p. 706)Therefore, although the field’s increased focus on studying interventions in real-world contexts is a positive development and has seen marked success, the fact that most of this work relies on traditional incentives raises questions about these interventions’ true applicability to real-world conflicts.…”
Section: Motivational Barriersmentioning
confidence: 99%
“…… Future research is needed to identify the characteristics that prejudice reduction interventions need to be scalable, and consideration should also be given to whether particular prejudice reduction interventions meet those criteria. (Hsieh et al, 2022, p. 706)…”
Section: Motivational Barriersmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, despite finding positive effects of intergroup interventions in the field, a recent meta-analytic study by Hsieh et al (2022, p. 706) concluded that "…there was no explicit and detailed consideration of how scalable effective interventions may be…Future research is needed to identify the characteristics that prejudice reduction interventions need to be scalable, and consideration should also be given to whether particular prejudice reduction interventions meet those criteria." Therefore, although the field's increased focus on studying interventions in real-world contexts is a positive development and has seen marked successes (Hsieh et al, 2022), the fact that many successful interventions rely on artificial incentives for participants to engage with them raises questions about their true applicability to real-world conflicts.…”
Section: Motivational Barriersmentioning
confidence: 99%